Minor Protease Inhibitor Mutations at Baseline Do Not Increase the Risk for a Virological Failure in HIV-1 Subtype B Infected Patients - Scherrer, Alexandra U.; Ledergerber, Bruno; von Wyl, Viktor; Böni, Jürg; Yerly, Sabine; Klimkait, Thomas; Cellerai, Cristina; Furrer, Hansjakob; Calmy, Alexandra; Cavassini, Matthias; Elzi, Luigia; Vernazza, Pietro L.; et al. (PLOS ONE, 2012)
Background Minor protease inhibitor (PI) mutations often exist as polymorphisms in HIV-1 sequences from treatment-naïve patients. Previous studies showed that their presence impairs the antiretroviral treatment (ART) response. Evaluating these findings in a larger cohort is essential. Methods To study the impact of minor PI mutations on time to viral suppression and time to virological failure, we included patients from the Swiss HIV Cohort Study infected with HIV-1 subtype B who started first-line ART with a PI and two nucleoside reverse transcriptase inhibitors. Cox regression models were performed to compare the outcomes among patients with 0 and ≥1 minor PI mutation. Models were adjusted for baseline HIV-1 RNA, CD4 cell count, sex, transmission category, age, ethnicity, year of ART start, the presence of nucleoside reverse transcriptase inhibitor mutations, and stratified for the administered PIs. Results We included 1199 patients of whom 944 (78.7%) received a boosted PI. Minor PI mutations associated with the administered PI were common: 41.7%, 16.1%, 4.7% and 1.9% had 1, 2, 3 or ≥4 mutations, respectively. The time to viral suppression was similar between patients with 0 (reference) and ≥1 minor PI mutation (multivariable hazard ratio (HR): 1.1 [95% confidence interval (CI): 1.0–1.3], P = .196). The time to virological failure was also similar (multivariable HR:.9 [95% CI:.5–1.6], P = .765). In addition, the impact of each single minor PI mutation was analyzed separately: none was significantly associated with the treatment outcome. Conclusions The presence of minor PI mutations at baseline has no effect on the therapy outcome in HIV infected individuals.